Growth performance and haematology of Isa-brown pullets fed diets containing graded levels of Centrosema pubescens leaf meal - Nwoga, C.C.; Agu, M.U.; Onodugo, M.O.; Ede, H.O.; Ugwuoke, J.I.; Ugwu, S.O.C. (Nigerian Journal of Animal Science, 2023)
This study was conducted to determine the effect of dietary levels of Centrosema pubescens leaf meal (CLM) on the growth performance and haematological parameters of pullets. Twenty-four, five weeks old Isa-Brown pullets were weighed and randomly allotted into three dietary treatment groups and was replicated twice with eight pullets per treatment and four pullets per replica in a completely randomized design (CRD). Each treatment was replicated two times giving four birds per replicate in a completely randomized design (CRD). Pullets were fed dietary levels of CLM at 0, 2.5 and 5% in T1, T2 and T3 respectively from the 5th week of age. Results on growth performance showed significant (P<0.05) difference in average daily feed intake. T3 had the highest average daily feed intake of 209.5±0.00 g. Results on haematology showed significant (P<0.05) differences in packed cell volume, red blood cell count, haemoglobin concentration, white blood cell count and lymphocyte. T3 had the highest packed cell volume, red blood cell count and haemoglobin concentration (29.00±0.58%, 29.00, 10.62±0.23x106/mm3 and 8.55±0.15g/100ml, respectively). T1 recorded the highest white blood cell count (11650±95.74x103/mm3). T1 and T2 had the highest lymphocyte levels (79.00±0.58). In conclusion, CLM should be incorporated in the diets of pullets up to 5% inclusion level to improve their average daily feed intake and some haematological parameters.